2012
DOI: 10.1074/jbc.m112.395533
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Iron-Sulfur Clusters in the Regulation of Transcription Factor Yap5-dependent High Iron Transcriptional Responses in Yeast

Abstract: Background: Saccharomyces cerevisiae responds to increased cytosolic iron through changes in the activity of the transcriptional activator Yap5. Results: A genetic screen identified a mutation in SSQ1 that prevented Yap5-dependent transcription. Conclusion: Reduced levels of proteins required for mitochondrial iron-sulfur cluster synthesis prevented Yap5-dependent transcription. Significance: The transcriptional response to low iron or high cytosolic iron is dependent on iron-sulfur clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 40 publications
0
58
0
Order By: Relevance
“…In that case, the metal starvation 34 or high intracellular availability 8,45 will affect the activity of iron-sulfur proteins involved in diverse metabolic functions required for microbial growth 46 . Ion exchange is a slow process and this can enlarge the biocidal effect of metal-based antimicrobials 47 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In that case, the metal starvation 34 or high intracellular availability 8,45 will affect the activity of iron-sulfur proteins involved in diverse metabolic functions required for microbial growth 46 . Ion exchange is a slow process and this can enlarge the biocidal effect of metal-based antimicrobials 47 .…”
Section: Resultsmentioning
confidence: 99%
“…Chandler and Segel 13 have demonstrated that inhibition of fungi growth by pyrithione is the result of the reduction in membrane transport systems. In addition, the source of ZnPT antifungal efficacy is related to the balance between the acquisition, storage and usage of metals by the fungus 45 .…”
Section: Resultsmentioning
confidence: 99%
“…In iron-sufficient WT cells, vacuolar iron exhibits a sextet that accounts for ϳ70% of spectral intensity. Much of the remaining intensity arises from mitochondrial iron, including a central quadrupole doublet that arises from [Fe 4 In our studies, the overall concentration of iron in cells grown on iron-deficient, iron-sufficient, and iron excess conditions is ϳ 200, 400, and 600 M iron, respectively. Iron-deficient cells are largely devoid of vacuolar iron; their Mössbauer spectra are dominated by the central doublet and an unusually strong NHHS Fe II doublet (5).…”
mentioning
confidence: 88%
“…2). Earlier studies suggested that Yap5 senses Fe cyt (31), but a later study (4) found that it senses mitochondrial ISC synthesis activity. When ISC synthesis is blocked, Yap5 transcription levels decline, and vacuoles no longer fill with iron (31).…”
mentioning
confidence: 99%
See 1 more Smart Citation